Symmetry Analysis of Double-ikat Textile Patterns: Patan Patola and Geringsing - Nyoman Dewi Pebryani (Institut Seni Indonesia Denpasar, 2018)
Symmetry analysis of textile patterns, which appear in the Patan Patola and Geringsing textiles produced by the double ikat technique in India and Indonesia, can provide information about the cultural relationship between ethnic groups. Symmetry is categorized into classes according to the Symmetry Group Theory. This article is based on a study in which eight textile samples were used: four Patan Patola textiles and four Geringsing textiles collected from an exhibition catalog. Each sample was examined based on the Symmetry Group Theory and divided into three class categories: point symmetry, one-dimensional, and two-dimensional classes. The results indicate high similarities among the symmetry classes of samples from these two ethnic groups, thereby suggesting that the patterns possess a common connection. Patan Patola and Geringsing textile patterns admittedÂ pmm2 andÂ d4in all samples, indicating intense interactions.